Men and women with human papillomavirus: focusingon the exposition risk and prevention - Alves, Maria D.S.; Barroso, Maria G.T.; Oriá, Mônica O.B (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: it is estimated that HPV infection increases four to six times the risk to acquire HIV by means of sexual transmissionObjective:weaimed to address HPV infection awareness among outpatients, highlighting gender differences concerning exposure, associated risk and prevention.Methods:this study was conducted in three Health Centers from Fortaleza. The sample was randomly chosen using the following criteria: subjectsfrom either sex, regardless of race, and socio-economic profiles who had submitted to a HPV treatment. The participants (100 men and 100 women)enrolled in this investigation have submitted to a guideline interview, previously developed by the authors in order to assess demographics anddetailed information about HPV awareness, contamination risk, and partners’ follow-up. Data analyses were conducted using Epi-Info 6.0 version.Results: concerning HPV’s knowledge, men (75%) and women (87%) confirmed that they were aware of the disease. When we asked the partici-pants about STD prevention, men (90%) and women (81%) were aware of the condom efficacy to prevent STD. Conclusion:our findings have con-firmed gender differences in coping with HPV infection. Additionally, our data will be helpful in building a HPV profile locally, which might sub-stantially improve sexual education programs towards the real necessities of our population.